The Liability of the Authorized Signatory in the Limited Liability Company (L.L.C) - Majd Walid Ata Al-Manasra (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to high light on the legal status of the authorized partner in the Limited Liability Company, whether he is in a frame of a partner, or within his position capacity frame (non-partner), This research is divided into three sections, the first section has addressed the characteristics of the Limited Liability Company through three sections, due to its mixed characteristics as it comprises within its frame both the characteristics of the joint-stock corporations and peoples companies, as to present the responsibility of the authorized signatory the second section has defined the methods of formation for such type of companies.While the third section addressed the responsibility of the authorized signatory in terms of the judgments of the Jordanian Cassation Court, that related to the title of the research, due to the lack of specialized legal provisions that govern the legal status of the authorized signatory for the Limited Liability Company within the Articles of the Jordanian Companies Law that devoted for the Limited Liability Companies.